The Relationship between Cognitive Function and Quality of Life in Patient with Intracranial Tumors at Haji Adam Malik Hospital Medan - Sari, Effi Rohani Nuzul; Rambe, Aldy Safruddin; Nasution, Irina Kemala (CoinReads Media Prima, 2023)
Introduction: Cognitive function, which is also known as the higher cortical function, is the most important aspect in determining the independence of patient. In patients with intracranial tumors, the presence of a tumor can directly affect cognitive function which affects quality of life. Quality of life is an important component in clinical neurooncology, especially intracranial tumors in determining the independence and choice of therapeutic approach. However, research related to the relationship between cognitive function and quality of life is still minimal. Method: This study used a cross-sectional method using an observational analytic approach in patients with intracranial tumors. The study subjects were 30 intracranial tumor patients and the MoCA-INA and Barthel Index were assessed. Results: Of the 30 research subjects, the majority were female (60.0%), average age 49.8 years, university education (50.0%), and Javanese ethnicity (53.3%). Headache is the most common manifestation (83.3%). Most of the patients had tumor involvement of one lobe (63.3%), and located in the parietal lobe (63.3%). There is a significant relationship between cognitive function and quality of life of intracranial tumor patients (p = 0.012). Conclusion: There is a relationship between cognitive function and quality of life of intracranial tumor patients.